Health Care Utilization by Preterm Infants with Respiratory Complications in Quebec - Jennifer S Landry; Dan Croitoru; Yulan Jin; Kevin Schwartzman; Andrea Benedetti; Dick Menzies (Canadian Respiratory Journal)
INTRODUCTION: Despite notable advances in prenatal and neonatal care, respiratory distress syndrome (RDS) and bronchopulmonary dysplasia (BPD) remain important complications of preterm births, and their long-term sequelae are poorly understood.